BEHAVIORAL FACTORS INFLUENCING AUDITOR JUDGMENT IN PUBLIC SECTOR AUDITS - Andi Nurrahma Gaffar; Amiruddin Amiruddin; Rahmawati HS (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze behavioral factors that influence auditor judgment in public sector audits through a literature review approach. Auditor judgment is a crucial element in the audit process because it determines the quality of findings, recommendations, and the reliability of audit reports. In the context of the public sector, which is rife with political pressure, accountability demands, and regulatory complexity, behavioral factors are becoming increasingly dominant in shaping auditors' professional decisions. This study integrates findings from various academic literature and relevant empirical research to identify key variables such as cognitive bias, time pressure, auditor experience, professional ethics, independence, and the influence of the organizational environment on auditor judgment. The results indicate that cognitive biases such as overconfidence and anchoring can reduce auditor objectivity in evaluating audit evidence. In addition, time pressure and high workloads tend to encourage auditors to make heuristic decisions, potentially reducing the quality of judgment. On the other hand, auditor experience and competence have been shown to improve the quality of professional judgment, especially in complex audit situations. Ethical and independence factors are also important determinants in maintaining the integrity of auditor judgment, especially in a public sector environment that is vulnerable to external intervention. This study confirms that improving the quality of auditor judgment depends not only on technical aspects but also requires strengthening behavioral aspects through training, an ethical organizational culture, and an effective internal control system.